The effects of zeolite and copper fertilizer application on the growth performance and yield of aerobic rice / Mohamad Fikri Abdul Rasid - Abdul Rasid, Mohamad Fikri (Faculty of Plantation and Agrotechnology, 2018)
Traditional paddy cultivation used lot of water to promote the growth of paddy. Due to this obstacle, research was made in order to produce more rice with less water used. Aerobic rice, made by MARDI was introduced to solve the problem. Copper (Cu) is an important micronutrient needed by paddy for metabolic process such as photosynthesis. If the Cu amount is insufficient, the paddy growth performance may reduce, grain may less filled and increase in spikelet sterility. Zeolite is a mineral that processed and can sustain the Cu2+. The problem that inspired the research was the function of Cu2+in growth performance of aerobic paddy and yield. The zeolite have the capability of holding and releasing of Cu2+. Four treatments and three replications was made. The copper as CuCl2was applied at 0, 15, 25, 50 ppm alongside of 150 g of zeolite per 100 kg of soil. Completely Randomized Design (CRD) experimental design was used during the experiment. The research was conducted in the green house for 12 week’s period to evaluate the effect of different levels of Cu application on the growth performance and yield of aerobic rice. The data retrieved from the experiment was analyzed using Minitab software on One-Way ANOVA and dependent t-test analysis method. The result shows increasing levels of copper in the soil do not significantly influenced the growth performance and yield of aerobic paddy. This happen due to several factors such as soil pH, organic matter content in soil, high concentration of Al/Fe oxide and other nutrients such as zinc, and the soil type.